2011
DOI: 10.1097/hpc.0b013e318204eb8b
|View full text |Cite
|
Sign up to set email alerts
|

A Report of Quality Improvement in the Care of Patients With Acute Coronary Syndromes

Abstract: Despite the existence and wide acceptance of guidelines for the treatment of patients with acute coronary syndromes, gaps in patient care still remain. To improve clinical processes of acute coronary syndromes care, a performance improvement (PI) continuing medical education (CME) program, a CME format approved by the American Medical Association, was developed. Clinician participants underwent a 3-stage process: (1) an initial patient chart review for self-assessment purposes, (2) the development and implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Several case studies have demonstrated that education, specifically Performance Improvement (PI) CME, improves clinical practice. [28][29][30][31][32][33][34][35] However, to our knowledge, data do not exist regarding the use of the PI CME format in the specialty of dermatology. PI CME helps physicians evaluate their practice and implement evidencebased strategies to overcome identified gaps, then remeasure their performance after these strategies have been implemented in their practice.…”
mentioning
confidence: 99%
“…Several case studies have demonstrated that education, specifically Performance Improvement (PI) CME, improves clinical practice. [28][29][30][31][32][33][34][35] However, to our knowledge, data do not exist regarding the use of the PI CME format in the specialty of dermatology. PI CME helps physicians evaluate their practice and implement evidencebased strategies to overcome identified gaps, then remeasure their performance after these strategies have been implemented in their practice.…”
mentioning
confidence: 99%
“…These efforts increased the likelihood that patients were treated on time with PCI [29], risk scores were documented [30] and the recommended discharge medication was prescribed [31]. Therefore the monitoring of guideline adherence as the foundation for targeted quality improvement efforts seems promising.…”
Section: Discussionmentioning
confidence: 99%
“…The most likely reason for the high rate of attrition was due to the time commitment required of PI CME activities. 29 This is an inherent problem often observed with PI CME activities. 29,30 Interestingly, a study examining the direct effect of PI participation on patient outcomes found minimal, if any, differences between patient outcomes among clinicians who completed various stages of PI.…”
Section: Discussionmentioning
confidence: 99%
“…29 This is an inherent problem often observed with PI CME activities. 29,30 Interestingly, a study examining the direct effect of PI participation on patient outcomes found minimal, if any, differences between patient outcomes among clinicians who completed various stages of PI. 31 Participation in the process of PI itself contributed to greater differences in patient outcomes as compared with didactic CME activities.…”
Section: Discussionmentioning
confidence: 99%